Composition of Oil from the Seeds of Cassia Sophera Linn. (Bangladesh Journal of Scientific and Industrial Research, 2007)
The oil obtained from the seeds of Cassia sophera Linn was analyzed by GC-MS and a total of 42 compounds have been identified. The major constituents are palmitic acid (22.82 %), linoleic acid (8.32 %), elaidic acid (19.16 %), stearic acid (9.86 %), 5-isopropyl -6-methyl-3-heptyne-2,5-diol (6.44 %), undecyl lauric acid (6.61 %), oleic acid (2.1 %), arachidic acid (3.57 %) and 3α, 7β-dihyodxy -5β, 6β-epoxycholestane (5.9 %). Bangladesh J. Sci. Ind. Res. 42(1), 75-78, 2007